Effect of an adapted physical activity program on the morphological and physiological profile of hypertensive patients of University Clinics of Kinshasa - Bofosa, Teddy; Miangindula, Betty; Kusuayi, Godefroid; Kiana, Nicaise; Nkiama, Constant (The European Research Journal, 2019)
Objectives: The treatment of arterial hypertension requires a comprehensive care because it is necessary not only to take the prescribed medication but also to apply certain rules of hygiene. The purpose of this study was to evaluate the effect of a program of physical activity adapted to the morphological and physiological state of the hypertensive patients. Methods: An experimental study was conducted on a sample of 31 male hypertensive patients with an average age of 58.16 ± 3.7 years undergoing an aerobic and anaerobic physical activity program treadmill walking, cycling, ergonomics and aerobic exercise and muscle building exercises of moderate intensity, duration of forty-five minutes and a frequency of three times a week associated with low calorie nutrition education low in cholesterol and saturated fatty acids (bad fats) , low sodium rich in vegetables, fruits and vitamins for 4 months at the University Clinics of Kinshasa between January 2017and May 2017. Results: After 4 months of intervention, we found statistically significant reductions in weight -7.2 kg, waist circumference -7.61 cm, body mass index -5.42 kg/m2, visceral fat percentage -1.4%, systolic blood pressure -6 mmHg, low-density lipoprotein -22 mg/dL, triglyceride -26.7 mg/dL with the exception of high-density lipoprotein and muscle that statistically increased +7.42 mg/dL and +15.3% while diastolic blood pressure -3.4 mmHg was not statistically modified. Conclusion: The practice of adapted physical activities combined with nutritional education improves the morphological and physiological status of hypertensive patients.